Teaching Research on the Design of High-speed Impellers Based on the Biomimetic Structure of an Owl’s Wing Feathers - 费思迪; 李金磊; 边艺菲; 吴 健; 王 川 (Education Research on Study Tours and Practice, 2025)
In order to design a high-speed and low-noise fan blade, using carved wing feathers as a bionic inspiration, this paper introduces structural optimization to the research and development of the fan. In addition, based on the "theory-simulation-practice" integrated teaching mode, bionic design and advanced manufacturing technology are organically combined to study the bladed disk vibration problem, and the high performance spiral case impeller is processed with carbon fiber material driven by engraving machine. The biomimicry of the sawtooth tail edge of carved wing, micron-scale grooves and nanopress micro teeth suppresses the noise caused by airflow separation and turbine separation, and improves the fluid dynamics of the surface of the blade. After modal simulation, imprint molding, fluid-structure coupling analysis, vibration suppression at high speed and complex surface machining are completed, and the noise reduction effect of impeller is more than 20 dB is achieved. Establishing an integrated teaching method based on "theory-simulation-practice" to develop students’ ability to think integratedly and practice engineering will provide a new way for future educational and teaching work.